Dissecting Taylor Rules in a Structural VAR - Choi, Woon (IMF Working Papers; Working Paper ;, 2010)
This paper uncovers Taylor rules from estimated monetary policy reactions using a structural VAR on U.S. data from 1959 to 2009. These Taylor rules reveal the dynamic nature of policy responses to different structural shocks. We find that U.S. monetary policy has been far more responsive over time to demand shocks than to supply shocks, and more aggressive toward inflation than output growth. Our estimated dynamic policy coefficients characterize the style of policy as a "bang-bang" control for the pre-1979 period and as a gradual control for the post-1979 period.